Development of Technology-based Non-Cognitive Diagnostic Assessment to Measure the Character of Mutual Cooperation and Learning Interest of Students (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study aims to describe the development of a technology-based non-cognitive diagnostic assessment to measure the cooperative character and learning interest of fourth-grade students at SD Negeri 03 Pontianak Selatan. The research method used in this study is research and development (R&D). The diagnostic assessment instrument was validated by assessment experts, subject matter experts, and media experts. The product was pilot-tested on 30 students and implemented on 75 students. Quantitative data were obtained from product validation, teacher and student response questionnaires. Qualitative data were obtained from interview results and product improvement notes from validators. The instruments used were validation sheets, interviews, and questionnaires. The results obtained were the feasibility of the non-cognitive diagnostic assessment development product based on word walls to measure the character of cooperation was 92.33% with the criterion of very feasible, while the non-cognitive diagnostic assessment development product based on websites was 99% with the criterion of very feasible; the practicality of the non-cognitive diagnostic assessment product development based on word walls was 84% with the criteria of very practical, and the practicality of the non- cognitive diagnostic assessment product development based on websites to measure interest was 90% with the criteria of very practicaland measuring learning interest and cooperative character with the help of technology effectively improved the curricular learning outcomes of IPAS lessons for fourth-grade students in class IV C from 78.96 to 93.61 with an N-gain of 0.54 (moderate category) and mathematics lessons in class IV B from 77.25. to 88.50 with an N-gain of 0.72 (high category). In conclusion, the development of a technology-based non-cognitive diagnostic assessment product to measure the spirit of mutual cooperation and learning interest of fourth-grade students is worth pursuing